Schrodinger Equation for the Hydrogen Atom - A Simplified Treatment - L. R. Ganesan; M. Balaji (E-Journal of Chemistry)
A simple method is presented here for solving the wave mechanical problem of the hydrogen atom. The normal method of converting the Cartesian coordinates into polar coordinates is tedious and also requires an understanding of the Legendre and Lagurre polynomials. In this paper we are using an alternative method, which requires only minimal familiarity with mathematical concepts and techniques.